Social Sciences : A Dying Fire - Ghimire, Kléber (Emerald Publishing, 2021)
Are the social sciences a dying fire? This book skilfully lays out how, apart from their misguided approach to knowledge production and specializations, social sciences continue to remain prisoners of a prescribed historical, cultural and anthropogenic narrative.